Observation on the Clinical Efficacy of Integrated Traditional Chinese and Western Medicine in the Treatment of Pityriasis Versicolor - Wang, Yan; Chen, Zhenlin (Journal of Contemporary Medical Practice, 2024)
Objective: Observation of the clinical efficacy and safety of traditional Chinese medicine decoction combined with benzimidazole cream in the treatment of pityriasis versicolor. Methods: 65 patients with pityriasis versicolor were randomly divided into an observation group (35 cases) and a control group (30 cases) according to the principles of randomization, control, and single blind. The control group was given an external application of 1% benzimidazole cream, while the observation group was given an external wash of traditional Chinese medicine decoction on the basis of the control group. One course of treatment was 10 days, and the total course of treatment was 20 days. Record the clinical efficacy and adverse reactions of two groups of patients after 10 and 20 days of medication, respectively. Results: After 2 courses of treatment, the overall effective rate, cure rate, and fungal microscopy negative rate of the observation group were better than those of the control group. Conclusion: Combination of Chinese and Western medicine in the treatment of pityriasis versicolor can further improve the efficacy, which is worth to be promoted and used in the clinic.